Absence of the -116A variant of the butyrylcholinesterase BCHE gene in Guarani Amerindians from Mato Grosso do Sul - Kelly Nunes; Ricardo L.R. Souza; Lupe Furtado-Alle; Luiza T. Tsuneto; Maria Luiza Petzl-Erler; Eleidi A. Chautard-Freire-Maia (Genetics and Molecular Biology, 2008)
Butyrylcholinesterase (BChE; EC 3.1.1.8; Online Mendelian Inheritance in Man (OMIM) number 177400) is an enzyme found in many human tissues and encoded by the BCHE gene, of which 65 variants have been identified. In a recent study we found that the -116A variant of exon 1 of the BCHE gene was associated with lower mean BChE activity. The present study analyzed the -116 single nucleotide polymorphism (SNP) in 253 Guarani Amerindian Brazilians from the state of Mato Grosso do Sul (148 Guarani-Kaiowá, 83 Guarani-Ñandeva and 22 Kaiowá-Ñandeva descendants) and verified that they were all homozygotic for the -116G variant. A comparative analysis of the -116 site in nine vertebrate species indicated the -116A variant as the ancestral type. This is the first study of the -116 SNP in Amerindians and it is therefore difficult to infer whether or not the -116A variant was always absent from southern paleo-Amerindians or was present and then subsequently lost due to evolutionary factors.